MATRIKS ATAS RING DERET PANGKAT TERGENERALISASI MIRING - Rugayah, Siti; Faisol, Ahmad; Fitriani, Fitriani (PATTIMURA UNIVERSITY, 2021)
Let R be a ring with unit elements, strictly ordered monoids, and a monoid homomorphism. Formed , which is a set of all functions from S to R with are Artin and narrow. With the operation of the sum of functions and convolution multiplication, is a ring, from now on referred to as the Skew Generalized Power Series Ring (SGPSR). In this paper, the set of all matrices over SGPSR will be constructed. Furthermore, it will be shown that this set is a ring with the addition and multiplication matrix operations. Moreover, we will construct the ideal of ring matrix over SGPSR and investigate this ideal's properties.